2003
DOI: 10.1128/aac.47.10.3332-3335.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of Klebsiella pneumoniae OmpK35 Porin in Antimicrobial Resistance

Abstract: OmpK35 from Klebsiella pneumoniae is the homologue of Escherichia coli OmpF porin. Expression of OmpK35 in K. pneumoniae strain CSUB10R (lacking both OmpK35 and OmpK36) decreased the MICs of cephalosporins and meropenem >128-fold and decreased the MICs of imipenem, ciprofloxacin, and chloramphenicol >8-fold. MIC reductions by OmpK35 were 4 times (cefepime), 8 times (cefotetan, cefotaxime, and cefpirome), or 128 times (ceftazidime) higher than those caused by OmpK36, but the MICs were similar or 1 dilution lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 18 publications
12
103
0
Order By: Relevance
“…Similar observations have been previously reported in K. pneumoniae isolates and generated an interesting debate concerning the selectivity of OmpK35 (10,25,27). We show here that in E. aerogenes, the activities of imipenem and cefepime, two zwitterionic molecules, are only weakly affected compared to large negatively charged drugs, and similar observations were reported with OmpK35 and OmpK36 (12,20,25). Interestingly, an S residue is located in the PhoE eyelet and has been reported to be involved in the rate of uptake of large negatively charged cephalosporins (29).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Similar observations have been previously reported in K. pneumoniae isolates and generated an interesting debate concerning the selectivity of OmpK35 (10,25,27). We show here that in E. aerogenes, the activities of imipenem and cefepime, two zwitterionic molecules, are only weakly affected compared to large negatively charged drugs, and similar observations were reported with OmpK35 and OmpK36 (12,20,25). Interestingly, an S residue is located in the PhoE eyelet and has been reported to be involved in the rate of uptake of large negatively charged cephalosporins (29).…”
Section: Discussionsupporting
confidence: 76%
“…aerogenes ATCC 15038 displays a marked difference in cephalosporin susceptibility when osmolarity conditions are modified. Interestingly, a recent study reported by Doménech-Sanchez et al (12) described the incidence of OmpK35 and OmpK36 expression on the K. pneumoniae susceptibility towards various antibiotics. Similar observations have been previously reported in K. pneumoniae isolates and generated an interesting debate concerning the selectivity of OmpK35 (10,25,27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of susceptibility to β-lactams, including cefepime, cefotetan, cefotaxime and cefpirome, in strains expressing OmpK35 is 4-8 times higher than that conferred by OmpK36 (rEF. 23). …”
Section: Alterations In Porin Expressionmentioning
confidence: 99%